Efeito do tipo de carvão injetado nas ventaneiras do alto-forno no consumo de combustíveis (Fuel-Rate) - Mauro Vivaldino Fernandes (2007)
Coal injection through of the blast furnaces tuyeres is one of the ways to reduce coke consumption and dependence in the blast furnace process in addition to lowering of cost of production of pig iron. There are increasing trends in achieving high substitution rates of coke through increased rates of coal injection and productivity. This topic hasbeen a great technological challenge and involves different aspects such as coal blending and characterization of blended mixtures and their influence on fuel replacement ratio and achieving process stability, high productivity and reduction in costs.The objective of the study was to evaluate a methodology for the calculation of the rate of substitution of coke by coal fines in the blast furnaces of Usiminas, Ipatinga, Brazil.The results show that the calorific power of injected coal has a decisive influence on replacement ratio. Besides, a model has been developed considering conditions of the blast furnaces in Usiminas relating variation of fuel-rate with injection rate and calorific power of the coal (or coal blends). The equivalent value achieved for the thermal input was 5000kcal for each kg in the fuel rate. For example, considering an injection rate of 100kg/t of pig iron, changing the coal with 7500kcal/kg by another, with 7700kcal/kg, the variation in the fuel rate is 4kg/t of pig iron.This correction in the variation of fuel rate (coke rate) contribute to the stability of process, once the changes of injected coals (or blends) brings operational variations in the blast furnace